Raman spectroscopy analysis of automotive paint for forensic purposes - Rojas-Rojas, Laura (2017)
Nowadays, the application of spectroscopic techniques in the analysis of forensic evidence is increasingly common due to its sensitivity and reliability. When evidence consists of fragments of automotive paint, microscopic and visual analysis techniques, in conjunction with other techniques, such as Raman and infrared spectroscopy, can help to identify the vehicle from which the fragment comes from. This paper shows that using Raman spectroscopy is very favorable in the analysis of small fragments of paint, because it allows establishing its origin by comparing profiles of different spectra. In addition, by this technique the identification of some of the constituents of the automotive paint such as: the polymeric matrix, the pigments and, other minor components can be performed. In Costa Rica, the use of Raman spectroscopy technique as part of a routine analysis in the Department of Forensic Sciences of the Organismo de Investigación Judicial (OIJ) is under development; therefore, the results of this research could contribute to its implementation.